Women in academic medicine leadership: correlation between sex of medical school deans and affiliated academic hospital system CEOs. Issue 2 (5th March 2020) - Marshall, Ariela L; Durani, Urshila; Mikhael, Joseph
Abstract : Background: Women are currently under-represented in 'C-suite' leadership positions at academic medical centres, including medical school deans, department chairs and hospital chief executive officers (CEOs). There are many potential reasons for the low percentage of women in academic medical leadership, including lack of mentorship and sponsorship, increased non-work responsibilities compared with men, implicit bias, and others. Methods: We collected data from 136 fully accredited US allopathic medical schools regarding sex of the medical school dean and sex of the CEO of the largest academic medical centre/teaching hospital affiliate. Schools where students rotate at non-academic centres were excluded from the final analysis, leaving 124 schools where we investigated the relationship between sex of US medical school dean and affiliated academic medical centre CEO. Results: 16.9% of current medical school deans and 17.7% of affiliated academic medical centre CEOs were female. Systems with one female leader were significantly (6.25-fold, 95% CI 2.22 to 17.56, p=0.001) more likely to have a second female leader, regardless of geographical region or institution type (public vs private). Conclusions: There is a significant positive association between medical school dean and affiliated academic hospital centre CEO sex. There are many potential factors that could contribute to this positive association, including mentorship, sponsorship and medical system consciousness about gender equity, among others. This relationship is important to recognise as we strive for more gender parity for women in positions of leadership in academic medicine.